Progeny evaluation in uniform nurseries - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1983)
Results are discussed and tables are included with the data obtained for bush and climbing beans grown in: (1) the Bean Team Nursery (VEF) between July 1-Dec. 31, 1981; (2) the 1981 Preliminary Yield Trial (EP), selected from the correspondent VEF reported the previous year; and (3) the 1980 International Bean Yield and Adaptation Nursery (IBYAN), whose accessions were selected from the EP of the same year. (CIAT)